Multiple familial glomangiomas with variable pathological findings. - Caprio, F.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2013)
Tumors originating from the glomus are made up of glomus cells, blood vessels and smooth muscle cells; according to the prevalence of these constituents, we distinguish solid glomus tumors, glomangioma and glomangiomioma, which seem variants of the same tumor or the same vascular malformation, due to mutations in the glomulin gene. In this report we describe a case of family glomangioma in two siblings and their mother. The histological examination of a mother’s lesion showed in the dermis a tumor of cuboidal cells arranged in parallel rows around vascular spaces lined by endothelial cells; there were not muscle cells. The histological examination of the two brothers showed the presence in the dermis of a neoformation consisting of large vascular spaces delimited by endothelial cells; there were not glomus cells, nor muscle cells.